THE ILLUMINATION OF THE CONCEPT OF MARGINALITY IN THE EYES OF MODERN UZBEK PSYCHOLOGISTS - Iskandarova Fotima Ibrohim kizi (Scientific Impulse, 2024)
This article examines the concept of marginality in the context of modern psychology in Uzbekistan. The author explores the problem of marginality from the socio-cultural and historical characteristics of the country and analyzes how this concept affects the psychological well-being of individual individuals. The article is based on current research and publications of Uzbek psychologists, as well as specific examples of the practice of psychological assistance in Uzbekistan.